2004
DOI: 10.2174/1570161043385510
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cardiovascular Changes in an Experimental Model of Syndrome X and Pharmacological Intervention on the Renin-Angiotensin- System

Abstract: Various cardiovascular risk factors and disease states similar to those present in type 2 diabetic patients also seem to be present in non-diabetic individuals. This cluster of risk factors has been called syndrome X, also known as metabolic cardiovascular syndrome or insulin resistance syndrome. Vascular wall components changes, including endothelial dysfunction and vascular smooth muscle cell (VSMC) migration and proliferation, could be involved in the cardiovascular alterations associated with this state. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 0 publications
3
24
0
Order By: Relevance
“…Previous studies have shown the key role of NAD(P)H-oxidase in the vascular oxidative stress, vascular smooth muscle cells proliferation, endothelial dysfunction, and development of hypertension. 4,5,20 Moreover, Nyby et al 33 have shown that increased ROS production by NAD(P)H-oxidase was associated with vascular inflammation assessed through VCAM-1 mRNA expression and vascular dysfunction in FFR. On the other hand, Sarr et al 34 showed that RW polyphenols prevented endothelial dysfunction, vascular ROS production, and NAD(P)H-oxidase expression in rats infused with angiotensin II-induced hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown the key role of NAD(P)H-oxidase in the vascular oxidative stress, vascular smooth muscle cells proliferation, endothelial dysfunction, and development of hypertension. 4,5,20 Moreover, Nyby et al 33 have shown that increased ROS production by NAD(P)H-oxidase was associated with vascular inflammation assessed through VCAM-1 mRNA expression and vascular dysfunction in FFR. On the other hand, Sarr et al 34 showed that RW polyphenols prevented endothelial dysfunction, vascular ROS production, and NAD(P)H-oxidase expression in rats infused with angiotensin II-induced hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Nox4 subunit expression is strongly correlated with an increase of NAD(P)H-oxidase activity. 6 Our group previously reported an enhanced NAD(P)H-oxidase aorta activity 5 and higher plasma lipid peroxidation 7 in FFR implying that this model of MS is characterized by oxidative stress.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Both high-fructose-and high-sucrose-fed rats show increased fasting glucose and triglyceride levels, and high-fructose-fed rats develop glucose intolerance and insulin resistance (5,6,17,18,25). Furthermore, several studies have found that a diet rich in fructose or sucrose induces hypertension in rats (11,26,33,40,44,45), whereas a few studies have reported that fructose does not affect blood pressure (BP) (1,41).…”
mentioning
confidence: 99%
“…Metabolic syndrome, characterized by hypertension, hyperglucemia, hyperlipidemia, is another well-known risk factor for cardiovascular disease (Isomaa et al, 2001;Miatello et al, 2004). Oxidative stress and vascular remodeling is also reported in this model Renna et al, 2009).…”
Section: Effects Of Organosulfur Compounds From Garlic On Animal Expementioning
confidence: 67%